Calciphylaxis of the breast with associated diffuse dermal angiomatosis - Magdalene Hope Maung; Judith Hugh (Elsevier, 2017)
In 2013, approximately 660,000 Americans had end stage renal disease (ESRD), requiring either dialysis or transplantation. Up to 5% of dialysis dependent patients may develop calcific uremic arteriolopathy or calciphylaxis (CPX) with vascular medial calcification of arterioles and subcutaneous capillaries with superimposed thrombotic occlusion. Risk factors other than chronic kidney disease include: female gender, diabetes mellitus, liver disease, warfarin, obesity, and hypercoagulability. CPX usually affects adipose rich areas on the trunk and proximal extremities, however an increasing number of reports document breast involvement. We report a case of unilateral breast CPX with a protracted clinical course and superimposed diffuse dermal angiomatosis (DDA). These two unusual cutaneous vaso-occlusive conditions have rarely been reported simultaneously. We review the literature and discuss the relationship and predisposing factors between these two conditions. We believe our case suggests that DDA could be precipitated by CPX secondary to calcific vaso-occlusion. Keywords: Calciphylaxis, Diffuse dermal angiomatosis, Breast